The role of opinion polls in coordination amongst protest voters: An experimental study - Oliver Feltham; Arthur Schram; Randolph Sloof (Tinbergen Institute, 2025)
In an election, protest voters signal their discontent with the party they traditionally support in different ways. This paper examines a specific form of protest voting in which voters choose an anti-mainstream party over their true first preference, the mainstream party, as a way to signal discontent with mainstream policies or influence future policy decisions. Protest voters face a trade-off stemming from a coordination problem. Too few protest votes mean that the strength of the protest is insufficient to affect the mainstream's policies; too many protest votes may result in an anti-mainstream victory, which is a sub-optimal outcome for the protest voter. One way to address this coordination problem is through opinion polls. In this context, polls serve a dual purpose: they provide information about the challenges protest voters face (information channel) and function as a coordination mechanism, allowing voters to adjust their behaviour based on poll results to resolve the coordination problem (coordination channel). We test, experimentally, the extent to which each of these channels increases the likelihood that the protest is successful and find that both channels are significant.
Keywords: C92; D72; D83; 330; protest voting; opinion polls; experiments